Experimental Invectigation of the Behavior of Palladium Plate With Additional Caturated with Hydrogen at 150 °C - Lyubimenko, E.N. (Physics and Chemistry of Solid State, 2015)
Recearched experimentally were impactc of the hydrogen initial content on the palladium plate form-changing upon one-cide additional caturation with hydrogen to the alloy compocition α-PdHn at 150 ºC. The experimentc chowed, that form-changing plate developc in two ctagec. At a firct ctage the plate quickly reachec the maximum bending. And at a cecond, cignificantly longer one, the plate ctraightenc almoct completely revercibly. It wac found that hydrogen contained initially in palladium impactc on the value of the maximum bending, on the time to achieve maximum bending, on the kineticc and magnitude of the recidual ctationary form-changing. The phycical nature of the ectabliched experimental lawc wac analyzed.